2020
DOI: 10.1177/0193945920946484
|View full text |Cite
|
Sign up to set email alerts
|

Project CaLM: A Pilot Intervention Integrating Mindfulness Strategies into Head Start Classrooms

Abstract: Using a participatory action research approach, this pilot project examined how mindfulness techniques could be integrated into classroom routines in Head Start programs, which serve children who live below the federal poverty line. In Study 1, we conducted limited-efficacy testing and examined the implementation of our intervention, which we refer to as Project CaLM (Children Learning Mindfulness). Although the study lacked adequate statistical power, when comparing the well-being of children who did and did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…All of the 10 studies indicated a positive change in behavioral regulation for children who participated in the MBIs. While some reported an overall positive direction of behavior change (Li-Grining et al, 2021 ; Wood et al, 2018 ), other studies revealed reductions in conduct and behavioral problems, including hyperactivity and aggression (Crooks et al, 2020 ; Janz et al, 2019 ; Moreno-Gómez and Cejudo, 2019 ), as indicated in teacher rating scales and reports. Several researchers also found significant increases in behavioral regulation and behavior control after their participation in MBIs (Lemberger-Truelove et al, 2018 ; Poehlmann-Tynan et al, 2016 ; Razza et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the 10 studies indicated a positive change in behavioral regulation for children who participated in the MBIs. While some reported an overall positive direction of behavior change (Li-Grining et al, 2021 ; Wood et al, 2018 ), other studies revealed reductions in conduct and behavioral problems, including hyperactivity and aggression (Crooks et al, 2020 ; Janz et al, 2019 ; Moreno-Gómez and Cejudo, 2019 ), as indicated in teacher rating scales and reports. Several researchers also found significant increases in behavioral regulation and behavior control after their participation in MBIs (Lemberger-Truelove et al, 2018 ; Poehlmann-Tynan et al, 2016 ; Razza et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies (Crooks et al, 2020 ; Jackman et al, 2019 ; Lemberger-Truelove et al, 2018 ; Li-Grining et al, 2021 ; Poehlmann-Tynan et al, 2016 ; Thierry et al, 2016 ; Zelazo et al, 2018 ) indicated that participants lived in economically disadvantaged communities, and one study recruited participants from a high trauma community (Razza et al, 2020 ). Though not all studies reported the types of early childhood programs, three studies were conducted in federally funded or subsidized preschools (Li-Grining et al, 2021 ; Jackman et al, 2019 ; Poehlmann-Tynan et al, 2016 ) and one study focused on a university based early childhood center (Wood et al, 2018 ). Five studies indicated that the majority of the participants were bilingual Hispanic or Latin X children (Lemberger-Truelove et al, 2018 ; Li-Grining et al, 2021 ; Moreno-Gómez and Cejudo, 2019 ; Thierry et al, 2016 ; Thierry et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations